FEASIBILITY OF PROCESS INTEGRATION IN THE OBTENTION OF TORULA YEAST - Rodríguez Castañeda, Yeini; de León Benítez, Juan Bautista; González Cortés, Meilyn; Machado Benavides, Serafín (Centro Azúcar Journal, 2014)
In this paper, the feasibility of energy integration is evaluated in the process of torula yeast, in order to diminishing the consumption of fuel oil in the process. We have to mention that the previously stated is possible from the heating of the dilution air, given in the generating oven of gases in the drying section, using the recovered thermal energy of currents of the own process. A study of the technological flow was carried out making emphasis in the drying stage of torula yeast. The hot and cold currents were identified in the process and mass and energy balances were carried out in order to determine the quantity of flow of each one starting from current data of the process. Two alternatives were considered: the energy integration, using all the fluids, and the heating of the air starting from the actual energy in the vinasses (hot fluid in the process). To carry out the energy integration, we used the software Hensad and with this, we determined the maximum temperature for heating the dilution air without the use of auxiliary services. The economic analysis was carried out evaluating three possible scenarios.